Elemen - Elemen Job Burnout dan Dampaknya terhadap Employee Performance - sarah imelda; Muhammad Fikri Ramadhan (Universitas Harapan Medan, 2022)
The purpose of this study was to determine the effect of work exhaustion, depersonalization, and decreased employee work performance partially and simultaneously toward employee performance. This type of research used an associative, the population was employees who worked in the company as many as 157 people, and sampling randomly so the number of research samples used was 100 respondents. Data sources are primary data and data collection techniques namely questionnaires. Data analysis techniques were multiple linear regression, classical assumption test, and hypothesis testing. Based on the results of the research conducted, it could be concluded that simultaneously work exhaustion, depersonalization and work performance have significantly affected employee performance in PT. Bank Sumut Cabang Medan. While work exhaustion and depersonalization partially have significantly affected employee performance, employee performance has no significant effect on employee performance in PT. Bank Sumut Cabang Medan. Job exhaustion, depersonalization, and work performance have a very strong relationship with performance. An adjusted R2 value of 0.786 means the performance of employees in PT. Bank Sumut Cabang Medan able to be explained by work exhaustion, depersonalization, and work performance amount of 78.60%, and the other 21.4% could be explained by other variables not examined